Development of an automated, microcultivation and analytical workflow for screening of peroxygenase producing K. phaffii strains - Philipp Dante Zinn (2023)
Bioprocess development has seen significant advancements in recent years, with a strong emphasis on automation to improve efficiency, productivity and to accelerate research. This thesis aimed to contribute to this field by developing an automated microcultivation and analytical workflow for the screening of peroxygenase producing Komagataella phaffii strains. The analytical workflow consists of an automated ABTS assay which demonstrated its robustness and consistency in determining the activity of the target enzyme, providing a crucial parameter for the screening process. Furthermore, the workflow allowed for automated measurement of protein concentrations via Bradford assay, aiding in the evaluation of peroxygenase expression levels. The results indicated that the automated assays were reliable and provided reproducible data. The target enzyme, peroxygenase, is regulated by a PDF promotor which is repressed in the presence of carbon sources such as glycerol or glucose. Hence, methanol is used to provide carbon for the protein biosynthesis of POX by taking advantage of the methanol utilization pathway and the PDF promotor of the engineered Komagataella phaffii strain. However, challenges were encountered in the production of peroxygenases in BioLector® microcultivations, requiring further investigation. The aim of the overlying EnzyPol project is to apply peroxygenase as a substitute for cobalt in curing of unsaturated polyester resins as a more sustainable, environmentally friendly and renewable alternative. This work contributes to the ongoing efforts in bioprocess development and demonstrates the benefits of lab-scale automation. By successfully developing an automated workflow for analysing POX activity, this thesis lays the foundation for high-throughput screening of POX producing Komagataella phaffii strains and optimal process parameters.
Keywords: Bioprocess development; automated microcultivation; peroxygenase; Komagataella phaffii